Efficacy of Chinese herbal medicine for stroke modifiable risk factors: a systematic review - Wenbo Peng; Romy Lauche; Caleb Ferguson; Jane Frawley; Jon Adams; David Sibbritt (BMC, 2017)
Abstract Background The vast majority of stroke burden is attributable to its modifiable risk factors. This paper aimed to systematically summarise the evidence of Chinese herbal medicine (CHM) interventions on stroke modifiable risk factors for stroke prevention. Methods A literature search was conducted via the MEDLINE, CINAHL/EBSCO, SCOPUS, and Cochrane Database from 1996 to 2016. Randomised controlled trials or cross-over studies were included. Risk of bias was assessed according to the Cochrane Risk of Bias tool. Results A total of 46 trials (6895 participants) were identified regarding the use of CHM interventions in the management of stroke risk factors, including 12 trials for hypertension, 10 trials for diabetes, eight trials for hyperlipidemia, seven trials for impaired glucose tolerance, three trials for obesity, and six trials for combined risk factors. Amongst the included trials with diverse study design, an intervention of CHM as a supplement to biomedicine and/or a lifestyle intervention was found to be more effective in lowering blood pressure, decreasing blood glucose level, helping impaired glucose tolerance reverse to normal, and/or reducing body weight compared to CHM monotherapy. While no trial reported deaths amongst the CHM groups, some papers do report moderate adverse effects associated with CHM use. However, the findings of such beneficial effects of CHM should be interpreted with caution due to the heterogeneous set of complex CHM studied, the various control interventions employed, the use of different participants' inclusion criteria, and low methodological quality across the published studies. The risk of bias of trials identified was largely unclear in the domains of selection bias and detection bias across the included studies. Conclusion This study showed substantial evidence of varied CHM interventions improving the stroke modifiable risk factors. More rigorous research examining the use of CHM products for sole or multiple major stroke risk factors are warranted.